Gender differences in the Force Concept Inventory for different educational levels in the United Kingdom - Matthew Mears (American Physical Society, 2019)
The Force Concept Inventory (FCI) is widely used to investigate the effect of education level on conceptual understanding of Newtonian mechanics but has only recently been scrutinized for gender effects and retention. This study examines both the gender gap in first year physics undergraduates compared to the gap for nonphysicists and the FCI retention after three months. All participants were either studying or working at the University of Sheffield in the UK and had completed a similar compulsory level of secondary education. As expected the results show that a greater level of education in physics is associated with a larger average FCI score. However, further analysis shows that there exists a gender gap at all levels of education. The size of the effect of gender is quantified using Cohen’s d and ranges from 0.84 to 1.17 which indicates a large effect due to gender for all levels of education. Despite the FCI having been used as a tool to measure learning gains immediately following instruction in Newtonian mechanics there has been little work to investigate whether this increase in FCI score remains after some time has elapsed. Here the increase in FCI scores is found to remain increased after a three month absence of mechanics-related teaching, and that this retention of FCI scores is independent of gender. Despite this, the gender gap still remains large and statistically significant after the three month delay.